Determinants of dividend policy of public listed companies in Malaysia - Yusof, Yusniliyana; Ismail, Suhaiza (Emerald Group Publishing Limited, 2016)
Purpose: This study investigates the determinants of the dividend policy of public listed companies in Malaysia. The factors examined in this study include earnings, cash flows, free cash flows, debt level, growth, investment, size, largest shareholders, risk, and lagged dividend. Design/methodology/approach: Data were obtained from the relevant databases and annual reports of the sampled companies. The study examines a total of 147 listed companies. In analyzing the data the study used fixed and random effects, pooled least square model, robust standard errors on fixed effects, and random effects models. Findings: The results revealed the five factors that are earnings, debt, size, investment, and largest shareholder have a significant influence on dividend policy with earnings, firm size and investment revealed to have a positive significant effect, whilst debt and large shareholders have a negative significant effect. Practical implications: The findings from this study are useful to the board of directors and management team of companies in deciding an appropriate dividend policy for the company. The results are also useful to shareholders in making investment decisions. Originality/value: The study extends empirical evidence on dividend policy determinants which are currently reported to be inconclusive. In addition, the study fills the lacuna in the existing literature by focusing on the issue of dividend policy determinants in the context of an emerging economy, namely Malaysia.